AWARENESS OF INFORMATION TECHNOLOGY AND ITS RELATIONSHIP TO THE CREATIVE ABILITY TO MANAGE THE LESSON AMONG PHYSICAL EDUCATION TEACHERS IN SECONDARY SCHOOLS IN THE RAMADI EDUCATION DIRECTORATE - Suad Hasan Saeed (Scholars Digest Publishing, 2024)
Scholars in the field of educational process and curriculum management have always sought to invest in information technology because of its importance in improving students' academic performance and developing their innovative abilities. Because one of the advantages of information technology is to make the learner feel excited and exciting and enhance his answers immediately, which motivates him to further study and scientific research based on these technologies. Therefore, this study aims to determine the degree of awareness of information technology and the degree of innovation in curriculum management among physical education teachers in secondary schools in the Ramadi Education Office and to know the relationship between the two. A sample of (110) teachers and schools were surveyed using the descriptive approach, the correlation method, with a percentage of (45.4%) of the total population. After the scales were distributed to teachers and school administrators, the results were collected and statistically processed. The researchers concluded that there is a statistically significant positive relationship between IT awareness and creative abilities in management courses. Therefore, the researchers recommend that they focus on providing information to physical education teachers about technology and how to use it to manage and direct physical education lessons in secondary schools. They also provide physical training and educational tools to high schools and invest in technology in teaching and training physical skills, investing time, energy and money to make learning more interesting and effective.
Keywords: IT awareness, creativity, lesson management.